Creating a Vertical Peeling Apparatus for Young Jackfruit Skins Employing Turning Process Technology - Hermawan, Muhammad; Ma'a, Mustaza; Yanda Zaira, Jupri; Wijianto, Agus (Aptek, 2025)
Young Jackfruit (Artocarpus heterophyllus) is a tropical fruit that grows in various regions, including Southeast Asia. While typically harvested when ripe, it is also consumed in its young stage. This final project focuses on the design and development of a Vertical Young Jackfruit Skin Peeling Machine utilizing the Turning Process Method. The proposed peeling machine is powered by a 1 hp motor with a speed of 1450 rpm, which is transmitted to 100 rpm. The machine's driving mechanism comprises a single transmission system, consisting of a pair of pulleys connected by a V-belt. When the motor is activated, the rotation is directly transmitted from pulley 1 to pulley 2, mounted on a 25 mm diameter shaft that rotates the young jackfruit using a V-belt intermediary. As the shaft rotates, a knife applies pressure on the rotating young jackfruit, moving from bottom to top. This movement is facilitated by a threaded shaft mechanism driven by the rotation of the fruit-driving shaft, which receives the rotational transmission from pulley 1 to pulley 2, mounted on a 25 mm diameter shaft to a 17 mm diameter shaft with a rotational speed of 40 rpm. The peeling process is conducted according to the dimensions of the young jackfruit, from bottom to top.